Early Intervention With Vedolizumab and Longer-term Surgery Rates in Crohn’s Disease: Post Hoc Analysis of the GEMINI Phase 3 and Long-term Safety Programmes - Dulai, Parambir S (J Crohns Colitis, 2020)
BACKGROUND: Crohn’s disease [CD] is a chronic inflammatory bowel disease that, with progression, may require surgical intervention. AIM: To determine whether vedolizumab treatment of CD earlier in the disease course [≤2 or ≤5 years of disease duration] influences risk of CD-related surgery after accounting for probability of response. METHODS: Post hoc analyses of data from CD patients treated with vedolizumab in the GEMINI 2, GEMINI 3, and GEMINI LTS trials [N = 1253] evaluated CD-related surgery [bowel resection or colectomy] with stratification by probability of response to vedolizumab [low/intermediate or high]. Analyses used a previously validated clinical decision support tool and both logistic regression and Cox proportional hazard analyses. RESULTS: In total, 113 [9.0%] vedolizumab-treated patients required CD-related surgery. Surgical rates were 6.1% and 9.8% for the high and low/intermediate probability of response groups, respectively. Risk of surgery was lower for patients with a high probability of response versus those with a low/intermediate probability of response (hazard ratio [HR] 0.50, 95% confidence interval [CI] 0.29 to 0.85). For patients with a low/intermediate probability of vedolizumab response, there was a consistent trend for association between earlier treatment [≤2 or ≤5 years since diagnosis] and a lower risk of surgery relative to later treatment (≤2 years versus >2 years: odds ratio [OR] 0.77, 95% CI 0.38 to 1.58; ≤5 years versus >5 years: OR 0.61, 95% CI 0.37 to 1.00]. CONCLUSIONS: Earlier intervention with vedolizumab may be associated with lower rates of surgery. Use of the clinical decision support tool may help identify patients most likely to benefit from earlier intervention with vedolizumab.